Trapping Entomopathogenic Fungi from Vine Terroir Soil Samples with Insect Baits for Controlling Serious Pests - Spiridon Mantzoukas; Ioannis Lagogiannis; Aristeidis Ntoukas; Panagiotis A. Eliopoulos; Demetrios Kouretas; Dimitrios G. Karpouzas; Konstantinos Poulas (Applied Sciences, 2020)
Fungi are eukaryotic microorganisms with many forms and certain demands about the soil they colonize, which reveal the conditions that prevail therein. Although they can often kill pests without damaging plants or humans, they are not widely used as pesticides as they are not easy to handle and require much time before they act. Nevertheless, insects can be used as baits to trap these entomopathogenic fungi, giving information about their distribution within the terroir. The purpose of this study was to investigate the soil distribution of entomopathogenic fungi species in soil samples from two vine soil terroirs. Nine fungi were identified in total, but M. anisopliae and B. bassiana showed the greatest frequency, which was expressed by difference in adult bait mortality among species. These fungi had not been previously documented in vine terroirs.